2004
DOI: 10.1136/ard.2003.007336
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus and genetic variation in the interleukin 1 gene cluster: a population based study in the southeastern United States

Abstract: Background: Interleukin (IL)1a and IL1b, and their endogenous receptor antagonist (IL1Ra), have been related to the pathology of systemic lupus erythematosus (SLE), but the role of IL1 polymorphisms in the aetiology of SLE is unknown. Objective: To examine polymorphisms at IL1a 2889(CRT), IL1a +4845(CRT), IL1b 2511(CRT), IL1b +3953(GRT), and IL1Ra (86 bp VNTR) in a population based study of SLE in North Carolina and South Carolina. Methods: Genotypes from 230 cases who met ACR classification criteria, and from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
2
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 15 publications
7
54
2
2
Order By: Relevance
“…31) Contradictory, there were two previous studies based on two different populations in Taiwan and Columbia reporting that there was no significant association. 28,29) In conclusion, our present study, it was observed that the IL-1β −511 and +3954 polymorphisms were significantly associated with the Malaysian SLE patients. The C and E1 alleles for the IL-1β −511 and +3954 polymorphisms, respectively, possessed a higher disease penetration to SLE.…”
Section: Analysis Of the Il-1β +3954 E1/e2 Polymorphismsmentioning
confidence: 67%
See 1 more Smart Citation
“…31) Contradictory, there were two previous studies based on two different populations in Taiwan and Columbia reporting that there was no significant association. 28,29) In conclusion, our present study, it was observed that the IL-1β −511 and +3954 polymorphisms were significantly associated with the Malaysian SLE patients. The C and E1 alleles for the IL-1β −511 and +3954 polymorphisms, respectively, possessed a higher disease penetration to SLE.…”
Section: Analysis Of the Il-1β +3954 E1/e2 Polymorphismsmentioning
confidence: 67%
“…It was also reported that the combined presence of IL-1α −889 C/C and IL-1β −511 T/T genotypes contributed to an increased risk of getting SLE among the African-Americans, but not in the Whites. 28) In Taiwan, Huang and his group had reported that there was no association between the IL-1β −511 polymorphisms and the susceptibility of SLE. 29) However, our present study of Malaysian SLE patients demonstrated that the C allele was significantly associated to this disease.…”
Section: Analysis Of the Il-1β −511 C/t Polymorphismsmentioning
confidence: 99%
“…On the contrary, the IL-1b À511 CT genotype and À511T allele were shown to be associated with SLE in African Americans but not in Whites from the Southeastern US. 29 IL-1b þ 3953 polymorphism was not associated with pSS in Finnish patients. 30 In Japanese, genotypes À511 CC and À31 TT were significantly less frequent in pSS patients than in healthy controls and SLE patients.…”
Section: Discussionmentioning
confidence: 79%
“…In SLE, however, IL-6 levels do not correlate with circulating CRP levels, as is the case in RA [103]. Genetic polymorphisms of CRP-inducing cytokines and their concomitant receptors have been found in association with SLE and might predispose to distinct clinical and immunological features [104][105][106][107].…”
Section: Sle and The Waste Disposal Hypothesismentioning
confidence: 99%